Role of chemoprophylaxis in outbreak control of pneumonia in an institutional setting - Sunil Diwate; D Nema; Arun Kumar Yadav (Journal of Marine Medical Society, 2024)
Background: The outbreak of pneumonia among young healthy recruits in military training establishments during winter months is well documented. Rapid gathering of recruits from all parts of the country in crowded living conditions exposes them to a variety of pathogens. The objective of the present investigation was to identify causes, establish diagnosis, imply control measures, and develop future strategies after the occurrence of pneumonia outbreak during winter. Methods: The outbreak was investigated using standard epidemiological methods and medical case sheets, X-ray findings, laboratory findings, etc., to describe the epidemiology and guide the control efforts. Results: Over 3 months, 67 cases of pneumonia occurred among recruits with an attack rate of 11.1/1000 recruits/month. Radiological positivity in the form of consolidation in chest X-ray was found in 100% of cases with complications like pleural effusion in seven cases, of which intercostal chest tube drainage was required in two cases. The outbreak responded rapidly following mass chemoprophylaxis with tablet azithromycin 500 mg in five doses. Conclusion: The outbreak of pneumonia occurred among young healthy recruits (age – 17–23 years) residing in an overcrowded dwelling. Mass chemoprophylaxis was a suitable strategy along with conventional remedial measures such as health advisories, health education, hand hygiene/respiratory hygiene etiquettes, and segregations of affected squads to control the outbreak.